The Role of Law Enforcement Officers in Handling Domestic Violence Cases in The Criminal Investigation Unit of The Southeast Aceh Police - Rahmayanti Rahmayanti; Suci Ramadani (Journal of Research in Social Science and Humanities, 2026)
Domestic Violence (DV) is a crime that has serious impacts on victims, both physically, psychologically, and socially. Case data in the jurisdiction of the Southeast Aceh Police shows an increase in the number of domestic violence cases from 2020 to 2024. This increase indicates low public legal awareness, strong patriarchal cultural factors, and a suboptimal victim protection system. This study formulates the problem regarding the obstacles faced by law enforcement officers, the legal efforts undertaken, and the role of law enforcement officers in handling domestic violence cases in the Criminal Investigation Unit of the Southeast Aceh Police. The purpose of this study is to analyze obstacles, examine the forms of legal efforts, and assess the effectiveness of the role of law enforcement officers based on the provisions of applicable laws and regulations. The research method used is empirical normative legal research with a statutory approach and a case approach, supported by domestic violence case data over the past five years. The results of the study indicate that obstacles to handling domestic violence include limited facilities and infrastructure, limited human resources, low victim participation in the legal process, and socio-cultural factors in the community. Legal efforts undertaken by law enforcement officers include preventive, repressive, and combined measures in accordance with the provisions of Law Number 23 of 2004 and criminal procedural law. The role of law enforcement officers is a determining factor in ensuring victim protection and the effectiveness of law enforcement. Therefore, strengthening institutional capacity, increasing the professionalism of officers, and increasing public legal awareness are necessary to ensure just and victim-oriented domestic violence law enforcement.